The effect of the process temperature on the bondability in transient liquid phase (tlp) diffusion bonding of AISI 430 ferritic stainless steel with nodular (spheroid) cast iron using a copper interlayer - Ozan, Sermin; Taskin, Mustafa; Kolukisa, Sedat (Carl Hanser Verlag, 2006)
The effect of the process temperature on the bondability in the transient liquid phase (tlp) was studied. The diffusion bonding of AISI 430 with nodular cast iron using a copper interlayer was investigated experimentally under a protective atmosphere at various temperatures and at a defined constant blow pressure which would cause macro deformation. Microstructure examinations were carried out with the help of optical microscopy, SEM and EDS. Hardness values were measured by HV scale under a load of 150 g. At the bond interface, decarburized and dechromised regions were observed on the ductile cast iron side and stainless steel side respectively. Best mechanical and metallurgical properties were observed for the specimen bonded at 1100 degrees C for 20 min. As a function of an elevation of the process temperature, an increase in the amount of graphite atoms that migrated toward the interface and a reduction at the nodular graphite diameters was noticed.
Die Auswirkung der Prozesstemperatur auf die Verschweißbarkeit beim Transient Liquid Phase (tip) -diffusionsfügen von rostfreien ferritischen AISI 430 Stählen mit Sphärogusseisen mit Hilfe einer Kupferzwischenlage